Clinical Outcomes of Neonatal Intensive Care Unit Graduates with Bridled Nasogastric Feeding Tubes - McBride, Elizabeth B.; Lasarev, Michael R.; O'Connell, Daniel M.; Limjoco, Jamie J. (American Journal of Perinatology, 2022)
Objective The aim of this study was to describe clinical outcomes of bridled nasogastric tube (NGT) program implementation for infants requiring assisted home feeding (AHF) to discharge from the neonatal intensive care unit (NICU).Study Design This was a descriptive prospective analysis of a pilot cohort of infants after implementation of a bridled NGT AHF program to facilitate discharge from level III and IV NICUs from March 2019 to October 2020.Results Of 29 attempts in infants, 22 infants were discharged with bridled NGTs over 18 months. Bridle placement was unsuccessful in three patients, and four bridles were removed before discharge. Bridle use ranged from 7 to 125 days, with a median duration of 37 days. Dislodgement rate was 0.69 per 100 days. Seventeen infants (77%) achieved full oral feeds, while five (23%) discharged with bridled NGTs later converted to gastrostomy tubes.Conclusion Implementation of a bridled NGT program is feasible for level III and IV NICUs to facilitate discharging infants who require feeding support to transition home.Key Points
Keywords: bridle; nasogastric feeding tube; gastrostomy tube; infant